2022
DOI: 10.1038/s41598-022-09467-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene knockdown of CCR3 reduces eosinophilic inflammation and the Th2 immune response by inhibiting the PI3K/AKT pathway in allergic rhinitis mice

Abstract: The CCR3 gene plays a critical role in allergic airway inflammation, such as allergic rhinitis (AR), and there is an inflammatory signal link between the nasal cavity and the CCR3 gene in bone marrow. However, the effects of the CCR3 gene in bone marrow cells on AR are not clear. The present study investigated the roles and underlying mechanisms of the bone marrow CCR3 gene in AR mice. Conditional knockout of the bone marrow CCR3 gene (CKO) in mice was generated using the Cre-LoxP recombination system, and off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“… 291 For mice lacking CCR3 gene in the bone marrow, the activity of PI3K/AKT signaling was also significantly reduced, and nasal eosinophil infiltration was inhibited; in addition, serum Th2 cytokines were reduced, and the symptoms of AR in mice were alleviated. 292 It was found in cell experiments that ST2/PI3K/mTOR-mediated autophagy is inhibited by IL-33 secreted by nasal epithelial cells, thereby promoting mast cell degranulation in allergic asthma. 293 …”
Section: Mechanismmentioning
confidence: 99%
“… 291 For mice lacking CCR3 gene in the bone marrow, the activity of PI3K/AKT signaling was also significantly reduced, and nasal eosinophil infiltration was inhibited; in addition, serum Th2 cytokines were reduced, and the symptoms of AR in mice were alleviated. 292 It was found in cell experiments that ST2/PI3K/mTOR-mediated autophagy is inhibited by IL-33 secreted by nasal epithelial cells, thereby promoting mast cell degranulation in allergic asthma. 293 …”
Section: Mechanismmentioning
confidence: 99%
“…These results suggest that CAE suppresses the cytokine secretion ability of Th2 cells but does not affect the proportion of Th2 cells in the spleen; furthermore, it improves the Th1/Th2 balance by increasing the proportion of Th1 cells, resulting in the alleviation of allergic symptoms. PI3K/AKT, MAPK, and NF-κB pathways are known to be involved in T cell activation and differentiation, contributing to allergic inflammation by promoting Th1/Th2 imbalance [ 9 , 10 , 11 , 12 , 13 ]. Our previous study suggested that cumin seed aqueous extract contains substances downregulating PI3K activation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cytokines such as interleukin (IL)-33, IL-25 and thymic stromal lymphopoietin (TSLP) are produced from mucosal epithelial cells when stimulated by antigens; additionally, these cytokines act on activated T-helper type-2 (Th2) cells to secrete Th2-type cytokines such as IL-4, IL-5, and IL-13, thereby increasing the allergic response [ 4 , 5 , 6 , 7 , 8 ]. Recent studies have shown that activation of the phosphatidylinositol-3- kinase (PI3K), mitogen-activated protein kinase (MAPK), and nuclear transcription factor κB (NF-κB) pathways contributes to T cell activation, function, and differentiation, leading to eosinophilic recruitment and T-helper type-1 (Th1)/Th2 imbalance [ 9 , 10 , 11 , 12 , 13 ]. In addition, the treatment of inhibitors showed a reduction in Th2 cytokine production and the degree of allergic symptoms [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allergic rhinitis (AR) is a type I allergic reaction in the nose triggered by exposure to speci c allergens in individuals with atopy, mediated by IgE and involving various cytokines and in ammatory mediators. The in ammation in AR primarily involves eosinophils, Th2 cells, and mast cells, which all express CCR3 on their surfaces [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%